The Role of Spiritual Well-being in Predicting Fear of COVID-19 Qmong Community-dwelling Older Adults in Iran - Hossein Khorany; Elnaz Takzare; Fatemeh Mohammadi; Seyedeh Ameneh Motalebi (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives: Fear is one of the most frequent feelings associated with coronavirus disease 2019 (COVID-19). Older people are at risk for severe COVID-19 infection. Spiritual well-being can play an important role in patients' coping and adaptation to stressful conditions. The present study aims to determine the role of spiritual well-being in predicting fear of COVID-19 among older adults in Qazvin, Iran.  Methods & Materials: This descriptive cross-sectional study was conducted on 400 community-dwelling older adults in Qazvin, Iran in 2021 who were selected using a cluster sampling method from public places in three urban areas. Data were collected using a demographic checklist, the Fear of COVID-19 Scale, and Paloutzian and Ellison's Spiritual well-being scale. A multivariate regression model was used to determine the predictors of fear of COVID-19. Results: The mean age of participants was 69.70±6.99 years. Their fear of COVID-19 was at a high level (Mean±SD=22±8.82). The results of regression analysis showed that sex (β=0.186, P=0.001), history of hypertension (β=0.130, P=0.006), history of diabetes (β=0.097, P=0.037), history of stroke (β=0.091, P=0.048), educational level (β=-0.142, P=0.007), economic status (β=0.145, P=0.007), and spiritual well-being (β=-0.117, P=0.013) were the predictors of fear of COVID-19.  Conclusion: Spiritual well-being, as well as educational level, history of chronic diseases, and economic status have a role in predicting the fear of COVID-19 in older adults. Therefore, the implementation of spirituality-related care programs can be useful for reducing the fear and anxiety of older adults during the COVID-19 pandemic.